2010
DOI: 10.1002/ana.21924
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier breakdown and repair by Src after thrombin‐induced injury

Abstract: Objective Thrombin mediates the life-threatening cerebral edema that occurs following intracerebral hemorrhage. Therefore, we examined the mechanisms of thrombin-induced injury to the blood-brain barrier (BBB) and subsequent mechanisms of BBB repair. Methods Intracerebroventricular (i.c.v.) injection of thrombin (20 U) was used to model intraventricular hemorrhage in adult rats. Results Thrombin reduced brain microvascular endothelial cell (BMVEC) and peri-vascular astrocyte immunoreactivity –indicating ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 38 publications
2
135
0
Order By: Relevance
“…121 Thus, Src kinase family members mediate acute BBB injury produced by thrombin, but also mediate chronic BBB repair. 121 Additional study of thrombin and blood products that induced BBB disruption and tissue injury after stroke may identify novel targets to reduce the effects of HT.…”
Section: Delayed Hemorrhagic Transformationmentioning
confidence: 99%
“…121 Thus, Src kinase family members mediate acute BBB injury produced by thrombin, but also mediate chronic BBB repair. 121 Additional study of thrombin and blood products that induced BBB disruption and tissue injury after stroke may identify novel targets to reduce the effects of HT.…”
Section: Delayed Hemorrhagic Transformationmentioning
confidence: 99%
“…For example, inhibition of the protein kinase Src can improve the acute outcome, such as neurodegeneration and abnormal behavior, after autologous blood injection in rats (96). On the other hand, prolonged inhibition of Src in the ICH model disturbs repair processes in the neurovascular niche that forms the blood-brain barrier (97), which might worsen long-term outcome. Notably, several drugs including G-CSF (64) and statins (73) have been reported to stimulate neurogenesis in hemorrhagic brain, but contribution of neurogenesis to the effects of these drugs in improving pathological and neurological parameters is unclear at present.…”
Section: Perspectivesmentioning
confidence: 99%
“…However, several studies have also shown that SFK inhibitors may have detrimental effects on cognition with prolonged use. For example, delayed PP2 administration given on days two through six post-TBI in one study extended BBB and brain edema disruption [51].…”
Section: Sfk Inhibitor Treatment: Promising Results and Future Directmentioning
confidence: 99%